Regional innovation system research trends: Toward knowledge management and entrepreneurial ecosystems - Pedro López-Rubio; Norat Roig-Tierno; Alicia Mas-Tur (International Journal of Quality Innovation, 2020)
The regional innovation system (RIS) is a popular way of explaining a region's development and competitiveness based on innovation activities and processes. In this paper, bibliometric techniques are used to analyze all RIS studies indexed in the Web of Science Core Collection (WoS CC) database as of December 2017. The goal of the analysis is to identify the main trends in RIS research. The evolution of the total number of publications and citations per year indicates that this research field has garnered considerable attention from the scientific community, public administrations, and international organizations. Analysis of the most common keywords and their co-occurrence sheds light on the conceptual framework of RIS research, where knowledge, innovation, clusters, policy, networks, systems, R&D, firms, and industry are key concepts. The 17 most influential RIS articles indexed in WoS CC are identified according to the total number of citations and the ratio of number of citations per year. Reviewing these 17 articles reveals 3 groups of underlying research trends: (1) research on innovation systems, which was mainly conducted in the 1990s, (2) research on knowledge management since the beginning of the 2000s, and (3) research on entrepreneurial ecosystems in recent years. Finally, analysis of citations to these 17 most influential RIS articles reveals strong interconnections according to the number of times they are cited together.
Keywords: 650; Regional innovation system; Innovation systems; Knowledge management; Entrepreneurial ecosystems; Bibliometrics; Web of Science